AuNPs@MIL-101 (Cr) as a SERS-Active Substrate for Sensitive Detection of VOCs - Xie, Dan; Wang, Ruimeng; Fu, Jinghao; Zhao, Zhongxing; Li, Min (Frontiers in Bioengineering and Biotechnology, 2022)
Surface-enhanced Raman scattering (SERS) is an important and powerful analytical technique in chemical and biochemical analyses. Metal–organic frameworks (MOFs) can effectively capture volatile organic compounds (VOCs) with high adsorption capacity and fast kinetics, and the local surface plasmon resonance characteristics of gold nanoparticles can quickly and effectively distinguish different VOCs by SERS. Combining both, we designed a novel SERS substrate based on embedding gold nanoparticles (AuNPs) within MIL-101(Cr) for the recognition of various VOCs in the gaseous phase. Occupying of AuNPs inside MIL-101(Cr) increased the micropore-specific surface area of AuNPs@MIL-101(Cr), which enabled AuNPs@MIL-101(Cr) to absorb more toluene molecules and consequently realized its high detection sensitivity. The detection limits for toluene, 4-ethylbenzaldehyde, and formaldehyde were down to 6, 5, and 75, ppm respectively. Moreover, this substrate could be used for detecting different VOCs simultaneously. Finally, we discussed the enhancement of AuNPs outside and inside MIL-101(Cr) on the Raman signal.